PENGELOLAAN PROYEK BISNIS BERBASIS SISTEM INFORMASI DALAM RANGKA DIGITALISASI PROSES BISNIS PERUSAHAAN PADA PT.AQUA - mesi suharni; Muhammad Irwan Padli Nasution,; Sri Suci Ayu Sundari (JEBS (Journal of Economic and Business Student), 2023)
In the world business, every company competes with each other to get a lot of profit and also the trust of customers, both new and old customers. Companies need a plan in developing information systems to continue to be able to adapt to the changing economic scope every year. The existence of developments in information systems requires strict supervision from the company, because if there is an error in the development process it will have quite a serious impact on the company. The development of a new system must carefully managed and orchestrated, and the way the project is on the road tends to be the most important factor affecting its outcome. That's why it's so important to have knowledge about managing information systems projects and unfortunately why their systems either succeed or fail.